2018
DOI: 10.1063/1.5040410
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of proton acceleration with multi-picosecond and high energy, kilojoule, lasers

Abstract: We use computational modeling to investigate proton beam generation from kilojoule, multi-picosecond laser pulses pertinent to several recently commissioned, large-scale laser facilities. The dependencies of proton acceleration on electron source parameters including pulse duration, temperature, and flux are independently and systematically evaluated. Proton acceleration is found to depend not only on the source size and peak temperature of the injected electrons but also on the rate of increase for a more phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For interactions with steep plasma density profiles, the dominant energy transfer mechanism is j×B heating [1,2]. In the presence of plasma densities less than critical (n c ≈ 10 −21 cm −3 ), simulations predict that electrons can gain energy by dephasing from a relativistic-intensity laser field [18][19][20][21][22][23][24][25]. The processes by which electrons dephase from the laser, however, are not well understood at sub-relativistic intensities.…”
mentioning
confidence: 99%
“…For interactions with steep plasma density profiles, the dominant energy transfer mechanism is j×B heating [1,2]. In the presence of plasma densities less than critical (n c ≈ 10 −21 cm −3 ), simulations predict that electrons can gain energy by dephasing from a relativistic-intensity laser field [18][19][20][21][22][23][24][25]. The processes by which electrons dephase from the laser, however, are not well understood at sub-relativistic intensities.…”
mentioning
confidence: 99%
“…The electron source method has been applied previously in similar problems 30 and benchmarked against full simulation of the laser 31 . The choice of an electron source with increasing slope temperature that exceeds that predicted by ponderomotive scaling for the laser intensity is a proven method for more accurately simulating proton acceleration from multi-picosecond pulses 38 . Longitudinal and lateral electric field maps were recorded periodically as were all species' densities, temperatures and velocities.…”
Section: Resultsmentioning
confidence: 99%
“…OMEGA EP, for example, is capable of delivering relativistically intense laser pulses (Iλ 2 >10 18 Wcm −2 μm 2 ) with kilojoule energies and multipicosecond pulse durations. Simulations suggest that the multipicosecond interaction will heat plasma electrons beyond the ponderomotive potential of the laser [24][25][26][27]. Indeed, recent experimental results have confirmed that these high energy, multipicosecond laser systems accelerate ions to maximum energies beyond those predicted by traditionally cited scaling laws [28][29][30].…”
Section: Introductionmentioning
confidence: 84%